Composite separation membrane, method for preparing the same, and use thereof in separating carbon dioxide

CN117919968BActive Publication Date: 2026-10-09SHANGHAI ECO POLYMER SCI & TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410126692.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2026-10-09
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

然而,FTM内的移动载体相对不稳定,因为载体在分离过程中,特别是在高湿度的烟道气条件下,很容易随着水蒸气流失掉

Benefits of technology

[0023]In the composite separation membrane described in this invention, amine compounds are firmly confined within the hydrogel matrix layer through electrostatic or hydrogen bonding interactions with negatively charged sulfonic acid or carboxylic acid groups. Carbon dioxide can undergo a reversible reaction with the amine compounds to form an intermediate that can rapidly diffuse within the hydrogel matrix layer. However, non-reactive gases, such as nitrogen, are blocked by the hydrogel matrix layer and cannot pass through. After optimizing the thickness of the hydrogel matrix layer and the loading of the mobile carrier (amine compounds), the resulting composite separation membrane achieves ultra-high CO2/N2 selectivity (>550) and simulates CO2 permeability of flue gas up to 1155 gas permeation units (GPUs, 1 GPU = 3.348 × 10⁻⁶). -10 mol m -2 s -1 Pa -1 This membrane outperforms most reported post-combustion carbon dioxide capture membranes. Furthermore, it exhibits remarkably stable separation performance during continuous testing exceeding 170 hours, attributed to the strong electrostatic interaction between the amine compound support and the hydrogel matrix material. The superior separation performance and high stability of this composite membrane indicate its significant potential for practical application in the field of carbon dioxide capture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117919968B_ABST
    Figure CN117919968B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of composite separation membrane and its preparation method and application in separating carbon dioxide, belong to separation membrane technical field.The composite separation membrane of the present application includes polymer substrate and separation layer;Separation layer is including hydrogel matrix layer and the amine compound permeated in hydrogel matrix layer;Hydrogel matrix layer is prepared by hydrogel matrix material and crosslinking agent.The amine compound in the composite separation membrane of the present application is firmly limited in hydrogel matrix layer by the electrostatic interaction or hydrogen bond interaction between the negative charge of sulfonic acid group or carboxylic acid group.Carbon dioxide can occur reversible reaction with amine compound, form intermediate, and the intermediate can rapidly diffuse in hydrogel matrix layer.But non-reactive gas, such as nitrogen, is blocked by hydrogel matrix layer and cannot pass through.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of separation membrane technology, and particularly relates to a composite separation membrane, its preparation method, and its application in the separation of carbon dioxide. Background Technology

[0002] With the rapid development of modern industry, the combustion of fossil fuels has become the main source of carbon dioxide (CO2) emissions into the atmosphere, causing a series of problems such as global warming, ocean acidification, and ecological damage. Carbon dioxide capture, utilization, and storage are considered key technologies for addressing global climate change. Among the many carbon capture technologies, membrane separation technology is considered a promising carbon dioxide capture technology due to its unique advantages such as high separation efficiency, low energy consumption, flexible operation, and environmental friendliness.

[0003] Polymer membranes have been widely studied for CO2 separation and capture. Currently developed polymer CO2 separation membrane materials include polyimide, polyvinylamino, polydimethylsiloxane, and polyether block polyamide. However, due to the trade-off effect between the permeability and selectivity of polymer materials—that is, the difficulty in simultaneously achieving high flux and high selectivity—polymer membranes are limited in large-scale CO2 capture applications. To overcome this inherent trade-off effect, much research has been conducted on preparing hybrid matrix membranes by adding nanofillers to the polymer matrix, such as covalent organic frameworks, metal-organic frameworks, porous organic cages, and zeolite molecular sieves. By combining the high porosity of porous fillers with the excellent machinability of polymers, CO2 permeability and CO2 / N2 selectivity are significantly improved. However, under flue gas conditions (temperature 50℃-90℃, humidity close to 100%), high temperatures and water vapor can lead to polymer chain aging and nanofiller damage. Flue gas typically contains 10%-15% water vapor, which limits the application of hybrid matrix membranes in flue gas carbon capture.

[0004] To achieve high CO2 separation performance under flue gas conditions, facilitated transport membranes (FTMs) based on the mechanism of stationary liquid membranes have been developed. In FTMs, CO2 and the support undergo a chemical reaction to form an intermediate that can rapidly migrate within the FTM membrane, significantly accelerating the transmembrane transport efficiency of CO2. Conversely, non-reactive molecules, such as nitrogen, methane, and hydrogen, have very low solubility in FTMs. Therefore, FTMs can achieve high CO2 / N2 selectivity while maintaining high CO2 permeability. However, the mobile support within the FTM is relatively unstable because it is easily lost with water vapor during separation, especially under high humidity flue gas conditions. Therefore, designing a matrix that can simultaneously ensure rapid support transport and prevent support loss during separation is crucial. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a composite separation membrane, its preparation method, and its application in carbon dioxide separation. This composite separation membrane exhibits high selectivity and permeability, making it particularly suitable for capturing and enriching carbon dioxide in flue gas.

[0006] The first objective of this invention is to provide a composite separation membrane comprising a polymer substrate and a separation layer; said separation layer comprising a hydrogel matrix layer and an amine compound permeated in said hydrogel matrix layer;

[0007] The hydrogel matrix layer is prepared from hydrogel matrix material and crosslinking agent.

[0008] In one embodiment of the present invention, the thickness of the separation layer is 0.2 μm-2 μm.

[0009] In one embodiment of the present invention, the polymer substrate is made of polyethersulfone, polysulfone, polyvinylidene fluoride or polyacrylonitrile; the pore size of the polymer substrate is 20nm-500nm.

[0010] In one embodiment of the present invention, the polymer substrate is in the form of a flat sheet membrane or a hollow fiber membrane.

[0011] In one embodiment of the present invention, the hydrogel matrix material is selected from one or more of sodium polyacrylate, sulfonated chitosan, sodium alginate, and sodium hyaluronate. The hydrogel matrix material is a cross-linked network structure containing sulfonic acid groups or carboxylic acid groups, which can maintain a stable structure in flue gas with high humidity. On the one hand, water molecules in the hydrogel matrix material can promote the reaction of amine compounds with CO2 to generate intermediates; on the other hand, a large number of water molecules form a continuous free volume in the hydrogel matrix layer, which is conducive to the rapid diffusion of amine compounds and intermediates in the hydrogel matrix layer. Simultaneously, due to interaction forces, amine compounds do not easily diffuse out of the hydrogel matrix material.

[0012] In one embodiment of the present invention, the crosslinking agent is selected from one or more of glutaraldehyde, water-soluble isocyanate and carbodiimide.

[0013] In one embodiment of the present invention, the amine compound is selected from one or more of ethanolamine, ethylenediamine, diethylenetriamine, piperazine, triethylenediamine, triethylenetetramine, and tetraethylenepentamine.

[0014] A second objective of this invention is to provide a method for preparing the aforementioned composite separation membrane, comprising the following steps:

[0015] S1. Dissolve the hydrogel matrix material and crosslinking agent in water to obtain a hydrogel matrix solution;

[0016] S2. The hydrogel matrix solution described in S1 is coated on the surface of the polymer substrate and left to stand to form a hydrogel matrix layer.

[0017] S3. The amine compound solution is coated on the surface of the hydrogel matrix layer described in S2. After standing, the amine compound permeates into the hydrogel matrix layer to form a separation layer, thus obtaining the composite separation membrane.

[0018] In one embodiment of the present invention, in S1, the concentration of the hydrogel matrix material in the hydrogel matrix solution is 20 g / L-100 g / L, for example, it can be 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, or 100 g / L; the amount of crosslinking agent added is 0.1%-5% of the mass of the hydrogel matrix material.

[0019] In one embodiment of the present invention, in S2, the standing is placed at room temperature for 0.5h-3h, during which the crosslinking agent and the polymer chains of the hydrogel matrix material react to form a hydrogel matrix layer with a crosslinked structure.

[0020] In one embodiment of the present invention, in step S3, the concentration of the amine compound solution is 20 g / L-400 g / L, for example, it can be 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, or 180 g / L. / L, 190g / L, 200g / L, 210g / L, 220g / L, 230g / L, 240g / L, 250g / L, 260g / L, 270g / L, 280g / L, 290g / L, 300g / L, 310g / L, 320g / L, 330g / L, 340g / L, 350g / L, 360g / L, 370g / L, 380g / L, 390g / L, 400g / L. In this step, amine compounds partially permeate into the hydrogel matrix layer.

[0021] A third objective of this invention is to provide an application of the aforementioned composite separation membrane in the separation of carbon dioxide.

[0022] The technical solution of the present invention has the following advantages compared with the prior art:

[0023] In the composite separation membrane described in this invention, amine compounds are firmly confined within the hydrogel matrix layer through electrostatic or hydrogen bonding interactions with negatively charged sulfonic acid or carboxylic acid groups. Carbon dioxide can undergo a reversible reaction with the amine compounds to form an intermediate that can rapidly diffuse within the hydrogel matrix layer. However, non-reactive gases, such as nitrogen, are blocked by the hydrogel matrix layer and cannot pass through. After optimizing the thickness of the hydrogel matrix layer and the loading of the mobile carrier (amine compounds), the resulting composite separation membrane achieves ultra-high CO2 / N2 selectivity (>550) and simulates CO2 permeability of flue gas up to 1155 gas permeation units (GPUs, 1 GPU = 3.348 × 10⁻⁶). -10 mol m -2 s -1 Pa -1 This membrane outperforms most reported post-combustion carbon dioxide capture membranes. Furthermore, it exhibits remarkably stable separation performance during continuous testing exceeding 170 hours, attributed to the strong electrostatic interaction between the amine compound support and the hydrogel matrix material. The superior separation performance and high stability of this composite membrane indicate its significant potential for practical application in the field of carbon dioxide capture. Attached Figure Description

[0024] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein:

[0025] Figure 1 This is a cross-sectional scanning electron microscope image of the composite separation membrane prepared in Example 1 of the present invention;

[0026] Figure 2 The energy dispersive X-ray spectrum of the composite separation membrane prepared in Example 1 of this invention;

[0027] Figure 3 The surface zeta potential diagram of the composite separation membrane prepared in Example 1 of the present invention;

[0028] Figure 4 This is a schematic diagram of the gas permeation device used in Embodiment 1 of the present invention;

[0029] Figure 5 The graph shows the gas separation performance of the composite separation membrane prepared in Example 1 of this invention under different temperature conditions.

[0030] Figure 6 This is a test graph showing the long-term CO2 / N2 separation performance of the composite separation membrane prepared in Example 1 of this invention;

[0031] Figure 7This is a graph showing the relationship between the concentration of sulfonated chitosan matrix and the thickness of the prepared composite separation membrane in Example 4 of the present invention.

[0032] Figure 8 This is a graph showing the gas separation performance of composite separation membranes of different thicknesses prepared in Example 4 of the present invention;

[0033] Figure 9 This is a test graph showing the long-term CO2 / N2 separation performance of the composite separation membrane prepared in Comparative Example 1 of this invention. Detailed Implementation

[0034] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.

[0035] In this invention, unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0036] In this invention, unless otherwise stated, the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0037] In this invention, unless otherwise specified, the experimental methods used in the embodiments of this invention are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0038] In this invention, unless otherwise stated, when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of the said feature, integral, step, operation, raw material, or component, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, raw materials, components, or combinations thereof.

[0039] In this invention, unless otherwise stated, the preparation of sulfonated chitosan used in the embodiments specifically includes the following steps: First, 40g of chitosan (degree of deacetylation ≥95%) is added to 2L of 1wt% acetic acid solution and stirred at 40°C for 1h; second, 50mL of 1,3-propanesulfonic acid lactone is added dropwise to the above chitosan solution under a nitrogen atmosphere, and the resulting mixture is stirred at 60°C for 6h; finally, the solution is slowly poured into a cold acetone solution, and a white precipitate is precipitated; after washing the solid three times with methanol, it is dried in an oven for 24h to obtain white powdered sulfonated chitosan.

[0040] In this invention, unless otherwise stated, the polyethersulfone porous membranes used in the examples and comparative examples were purchased from Haining Yibo Filter Material Factory, and are in the form of flat sheet membranes with a pore size of approximately 100 nm.

[0041] Example 1

[0042] The composite separation membrane and its preparation method of the present invention specifically include the following steps:

[0043] S1. Dissolve 80g of sulfonated chitosan matrix in 1L of water, and then add 2.7mL of 50% glutaraldehyde aqueous solution to form sulfonated chitosan matrix solution.

[0044] S2. Use a scraper to coat the above sulfonated chitosan matrix solution onto the surface of the polyethersulfone porous membrane and keep it at room temperature for 30 minutes to form a cross-linked sulfonated chitosan hydrogel matrix layer.

[0045] S3. A certain amount of 320g / L diethylenetriamine solution is scraped onto the surface of the sulfonated chitosan hydrogel matrix layer and left at room temperature for 2 hours to allow the diethylenetriamine to penetrate into the sulfonated chitosan hydrogel matrix layer and form a composite separation membrane.

[0046] Cross-sectional scanning electron microscope image of the composite separation membrane is shown below. Figure 1 As shown, from Figure 1 It can be seen that the thickness of the separation layer is 1.2 μm.

[0047] To confirm the successful loading of diethylenetriamine into the sulfonated chitosan hydrogel matrix layer, energy-dispersive X-ray spectroscopy was used to analyze the elemental composition of the separation layer. Figure 2 It can be seen that C, O, N, and S elements are uniformly distributed in the separation and selection layer of the membrane loaded with diethylenetriamine, and the nitrogen content is 18.1%, which is higher than that of the sulfonated chitosan matrix membrane (7.3%). Infrared spectroscopy characterization of the membrane after loading with diethylenetriamine revealed a nitrogen content of 3319 cm⁻¹. -1 1635cm -1 and 815cm -1 The characteristic absorption peak of -NH2 appeared at the location, which is attributed to the introduction of diethylenetriamine.

[0048] To verify the electrostatic interaction between the sulfonic acid groups in the sulfonated chitosan matrix and the protonated amine in diethylenetriamine, the surface zeta potentials of the sulfonated chitosan matrix and the sulfonated chitosan matrix after conjugation with diethylenetriamine were measured, and the results are as follows: Figure 3 As shown. From Figure 3It can be seen that the isoelectric point of the sulfonated chitosan matrix is ​​approximately 4.55, and the zeta potential in a neutral environment is approximately -16.26 mV. When the pH increases from 3.1 to 10.0, the surface zeta potential decreases from 10.3 mV to -32.4 mV, indicating that the abundant sulfonic acid groups in the sulfonated chitosan create a strongly negatively charged environment. The isoelectric point of the sulfonated chitosan matrix after conjugation with diethylenetriamine is approximately 6.3, and the zeta potential in a neutral environment is approximately -4.8 mV, indicating that the negative charge on the sulfonated chitosan is partially neutralized by the protonated diethylenetriamine. These results indicate that the diethylenetriamine molecules are confined within the negatively charged sulfonated chitosan matrix by electrostatic forces.

[0049] To test the carbon capture performance of the composite separation membrane, a gas permeation device was built to evaluate the membrane's CO2 / N2 separation performance. Figure 4 A CO2 / N2 mixture with a volume fraction of 10%:90% was used as the simulated flue gas, which entered the membrane tank from the feed side after passing through a humidifier. The purge gas carried the permeate to a gas chromatograph for component analysis. The CO2 separation performance of the diethylenetriamine-loaded composite membrane was studied within a temperature range of 65℃-90℃, and the results are as follows: Figure 5 As shown. From Figure 5 It can be seen that CO2 permeability increases exponentially with increasing temperature. It is 334 GPU at 65℃, increases to 539 GPU at 75℃, further increases to 810 GPU at 85℃, and finally reaches 1155 GPU at 90℃. The CO2 / N2 selectivity also increases with increasing temperature, from 678 at 65℃ to 952 at 75℃. This is mainly due to the increase in CO2 permeability. However, the selectivity decreases to 557 at 90℃ because N2 diffuses faster at higher temperatures. CO2 permeability increases exponentially with increasing temperature and follows the Arrhenius relation.

[0050] To evaluate the stability of the prepared diethylenetriamine-loaded composite separation membrane, a long-term test was conducted at 85°C. The results are as follows: Figure 6 As shown. From Figure 6 It can be seen that even at a high temperature of 85℃, the membrane can still maintain long-term stability (fluctuation <7%) for up to 170h, with an average CO2 permeability of 730 GPU and an average CO2 / N2 selectivity of 700. This far exceeds most reported transport-enhancing membranes (long-term stability less than 80h).

[0051] Example 2

[0052] The composite separation membrane and its preparation method of the present invention specifically include the following steps:

[0053] S1. Dissolve 80g of sulfonated chitosan matrix in 1L of water, and then add 2.7mL of 50% glutaraldehyde aqueous solution to form sulfonated chitosan matrix solution.

[0054] S2. Use a scraper to coat the above sulfonated chitosan matrix solution onto the surface of the polyethersulfone porous membrane and keep it at room temperature for 30 minutes to form a cross-linked sulfonated chitosan hydrogel matrix layer.

[0055] S3. A certain amount of 320g / L tetraethylenepentamine solution is scraped onto the surface of the sulfonated chitosan hydrogel matrix layer and left at room temperature for 2 hours to allow the tetraethylenepentamine to penetrate into the sulfonated chitosan hydrogel matrix layer and form a composite separation membrane.

[0056] Energy-dispersive X-ray spectroscopy and infrared spectroscopy also confirmed that amine molecules were loaded into the sulfonated chitosan matrix. At 65 °C, the composite separation membrane loaded with tetraethylenepentamine molecules exhibited a CO2 permeability of 464 GPU and a CO2 / N2 selectivity of 1094. This experiment demonstrates that the sulfonated chitosan matrix has a stabilizing effect on tetraethylenepentamine.

[0057] Example 3

[0058] The composite separation membrane and its preparation method of the present invention specifically include the following steps:

[0059] S1. Dissolve 80g of sulfonated chitosan matrix in 1L of water, and then add 2.7mL of 50% glutaraldehyde aqueous solution to form sulfonated chitosan matrix solution.

[0060] S2. Use a scraper to coat the above sulfonated chitosan matrix solution onto the surface of the polyethersulfone porous membrane and keep it at room temperature for 30 minutes to form a cross-linked sulfonated chitosan hydrogel matrix layer.

[0061] S3. Apply a certain amount of piperazine solution with a concentration of 200g / L to the surface of the sulfonated chitosan hydrogel matrix layer and leave it at room temperature for 2 hours to allow the piperazine to penetrate into the sulfonated chitosan hydrogel matrix layer and form a composite separation membrane.

[0062] Energy-dispersive X-ray spectroscopy and infrared spectroscopy also confirmed that amine molecules were loaded into the sulfonated chitosan matrix. At 65°C, the composite separation membrane loaded with piperazine molecules exhibited a CO2 permeability of 360 GPU and a CO2 / N2 selectivity of 562. This experiment demonstrates that the sulfonated chitosan matrix also has a stabilizing effect on piperazine molecules.

[0063] Example 4

[0064] The composite separation membrane and its preparation method of the present invention specifically include the following steps:

[0065] S1. Dissolve 40g, 60g, 80g, and 100g of sulfonated chitosan matrix in 1L of water, respectively, and then add 1.4mL, 2.0mL, 2.7mL, and 3.4mL of 50% glutaraldehyde aqueous solution to form matrix solutions A, B, C, and D.

[0066] S2. Use a scraper to apply the above matrix solutions A, B, C, and D onto the surface of the polyethersulfone porous membrane and keep it at room temperature for 30 minutes to form a cross-linked sulfonated chitosan hydrogel matrix layer.

[0067] S3. A certain amount of 320g / L diethylenetriamine solution is scraped onto the surface of the above sulfonated chitosan hydrogel matrix layer and left at room temperature for 2 hours to allow the diethylenetriamine to penetrate into the sulfonated chitosan hydrogel matrix layer and form a composite separation membrane.

[0068] The thicknesses of the composite separation membranes prepared from matrix solutions A, B, C, and D were characterized using scanning electron microscopy, and the results are as follows: Figure 7 As shown. From Figure 7 It can be seen that the thickness of the composite membrane increases linearly from 0.4 μm to 1.6 μm with increasing sulfonated chitosan concentration. Simultaneously, the CO2 flux also gradually increases from 460 GPU to 580 GPU with increasing composite membrane thickness. When the composite membrane thickness further increases to 1.6 μm, the CO2 flux decreases slightly to 520 GPU. Figure 8 The results show that as the composite membrane thickness increases, more diethylenetriamine molecules are composited, thereby promoting the permeation of more CO2 through the separation membrane. When the separation membrane thickness is greater, the transmembrane resistance also increases, affecting the separation flux.

[0069] Example 5

[0070] The composite separation membrane and its preparation method of the present invention specifically include the following steps:

[0071] S1. Dissolve 90g of sodium alginate matrix in 1L of water, and then add 3mL of 50% glutaraldehyde aqueous solution to form sodium alginate matrix solution.

[0072] S2. Use a scraper to apply the above sodium alginate matrix solution to the surface of the polyethersulfone porous membrane and keep it at room temperature for 30 minutes to form a cross-linked sodium alginate hydrogel matrix layer.

[0073] S3. A certain amount of 320g / L diethylenetriamine solution is scraped onto the surface of the sulfonated chitosan hydrogel matrix layer and left at room temperature for 2 hours to allow the diethylenetriamine to penetrate into the sodium alginate matrix and form a composite separation membrane.

[0074] Scanning electron microscopy (SEM) images of the surface and cross-section of the composite separation membrane show that the separation layer thickness is 1.5 μm. Energy dispersive X-ray spectroscopy (EDS) and infrared spectroscopy also confirmed that amine molecules were loaded into the sodium alginate matrix. At 65 °C, the composite separation membrane loaded with diethylenetriamine exhibited a CO2 permeability of 564 GPU and a CO2 / N2 selectivity of 652, maintaining stable operation for over 150 h. This indicates that diethylenetriamine is stably integrated into the sodium alginate matrix and acts as a CO2-promoting carrier, achieving efficient CO2 / N2 separation.

[0075] Comparative Example 1

[0076] S1. Dissolve 80g of chitosan matrix in 1L of 1% acetic acid solution, and then add 2.7mL of 50% glutaraldehyde aqueous solution to form chitosan matrix solution.

[0077] S2. Use a scraper to coat the above chitosan matrix solution onto the surface of the polyethersulfone porous membrane and keep it at room temperature for 30 minutes to form a cross-linked sulfonated chitosan hydrogel matrix layer.

[0078] S3. A certain amount of 320g / L diethylenetriamine solution is scraped onto the surface of the sulfonated chitosan hydrogel matrix layer and left at room temperature for 2 hours to allow the diethylenetriamine to penetrate into the sulfonated chitosan hydrogel matrix layer and form a composite separation membrane.

[0079] The thickness of the composite separation membrane obtained by scanning electron microscopy was consistent with that of the composite separation membrane in Example 1, with a separation layer thickness of approximately 1.2 μm. The initial content of diethylenetriamine in the chitosan matrix membrane was also the same. However, during long-term separation tests, it was found that the CO2 permeability of the chitosan separation membrane loaded with diethylenetriamine decreased significantly in the first 10 hours, and after 120 hours, it dropped to less than 50% of its initial value. Figure 9 This is mainly because chitosan lacks negatively charged groups, resulting in weak interactions between diethylenetriamine and the matrix, making it prone to leaching from the matrix. This comparative experiment also confirmed the stabilizing effect of negatively charged groups in the matrix on the amine carrier.

[0080] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A composite separation membrane, characterized in that, It includes a polymer substrate and a separation layer; the separation layer comprises a hydrogel matrix layer and an amine compound permeated in the hydrogel matrix layer; the amine compound is selected from one or more of ethanolamine, ethylenediamine, diethylenetriamine, piperazine, triethylenetetramine, and tetraethylenepentamine; The hydrogel matrix layer is prepared by a hydrogel matrix material and a crosslinking agent; the hydrogel matrix material is selected from one or more of sodium polyacrylate, sulfonated chitosan, sodium alginate and sodium hyaluronate.

2. The composite separation membrane according to claim 1, characterized in that, The thickness of the separation layer is 0.2μm-2μm.

3. The composite separation membrane according to claim 1, characterized in that, The polymer substrate is made of polyethersulfone, polysulfone, polyvinylidene fluoride, or polyacrylonitrile; the pore size of the polymer substrate is 20 nm-500 nm.

4. The composite separation membrane according to claim 1, characterized in that, The crosslinking agent is selected from one or more of glutaraldehyde, water-soluble isocyanate and carbodiimide.

5. A method for preparing the composite separation membrane according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Dissolve the hydrogel matrix material and crosslinking agent in water to obtain a hydrogel matrix solution; S2. The hydrogel matrix solution described in S1 is coated on the surface of the polymer substrate and left to stand to form a hydrogel matrix layer. S3. The amine compound solution is coated on the surface of the hydrogel matrix layer described in S2. After standing, the amine compound permeates into the hydrogel matrix layer to form a separation layer, thus obtaining the composite separation membrane.

6. The method for preparing the composite separation membrane according to claim 5, characterized in that, In S1, the concentration of the hydrogel matrix material in the hydrogel matrix solution is 20 g / L-100 g / L, and the amount of crosslinking agent added is 0.1%-5% of the mass of the hydrogel matrix material.

7. The method for preparing the composite separation membrane according to claim 5, characterized in that, In S3, the concentration of the amine compound solution is 20 g / L to 400 g / L.

8. The application of the composite separation membrane according to any one of claims 1-4 in the separation of carbon dioxide.

Citation Information

Patent Citations

  • Gas separation membrane and its utilization

    JP2008068238A